PTH-230 Increased prevalence of bile acid malabsorption in patients with breast cancer and chronic diarrhoea. (22nd June 2015) - Klimova, K; Lalji, A; Muls, A; Andreyev, J
Abstract : Introduction: Bile acid malabsorption (BAM) is has been increasingly recognised as a cause of chronic diarrhoea, and forms part of differential diagnosis of new-onset diarrhoea after pelvic radiotherapy. Its prevalence in patients with erratic bowel function after treatment for breast cancer has not been studied. Method: Between January 2006 and September 2014, 108 patients with breast cancer were referred to our clinic due to gastrointestinal symptoms. Of those, 66 had chronic diarrhoea (intermittent on continuous type 6–7 stools on Bristol Stool Chart and increased frequency) and/or other symptoms. 23 of them were included in the study as they underwent a SeHCAT scan. The baseline characteristics, most frequent gastrointestinal symptoms and types and doses of cancer treatment received were recorded. Results: The mean age was 59.95 (range 41–79) years, 14 patients had left breast cancer, 8 right breast cancer and 1 bilateral breast cancer. 20/23 patients received radiotherapy, 19/23 underwent surgery, all 23 were treated with chemotherapy (cyclophosphamide 17/23, fluorouracil 14/23, epirubicin 13/23, paclitaxel 7/23, doxetaxel 5/23), and 9 with oral hormonal therapy. Their most frequently reported gastrointestinal symptoms were urgency (11 of 23 patients), abdominal bloating, frequency, loose stools and steatorrhoea (10 of 23 patients), abdominal pain (8 of 23 patients) and flatulence (7 of 23 patients). BAM was then diagnosed in 13/23 patients (56.5%). There were no statistically significant differences between patients with and without BAM in types of treatment administered, dose of chemotherapy or total radiation dose and both groups of patients had similar baseline characteristics. BAM was treated with low fat diet in 10/13 patients, and bile acid sequestrant colesevelam was added in 7/13 patients. Conclusion: The prevalence of BAM in breast cancer patients treated with multiple therapy modalities and erratic bowel function is higher than in normal population. Further studies are necessary to establish possible aetiological associations for its development. Disclosure of interest: None Declared. Reference: Andreyev J. Gastrointestinal problems after pelvic radiotherapy: the past, the present and the future. Clin Oncol. 2007;19:790–9